Learning Multimedia Management Strategy at Home During Learning from Home - Budi Sulistiyo Nugroho; Abdul Wahab Syakhrani; Alim Hardiansyah; Petrus Jacob Pattiasina; Emy Yunita Rahma Pratiwi (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
The extraordinary development of technology followed by changes in human life in all fields also impacts the behavior of technology users and consumer behavior than multimedia, all of which have accelerated changes both in terms of multimedia transformation and in the form of business models that use multimedia. This study will discuss how multimedia strategies and their sustainable governance will impact distance learning that has been practiced so far as part of the effort to respond, namely learning from home. Because the impact of this media is quite significant, the parties, including parents who have to guide their children's learning, must also get a good understanding of how their strategy is to manage multimedia management for their children's learning considering that today multimedia technology has become like food that must be adequately served, really not contaminated with viruses or other toxins. This study utilizes data from the latest findings from previous publications from the book, journals, and other websites that contribute to the voice of technology and its impact on its users. Based on the results of the study of these data sources and a very detailed discussion, we finally got a new entry where parents must gain an understanding of multimedia applications and also how to use them and their uses so that parents and students can take advantage of multimedia for their learning success and life.